Enhancing Accounting Proficiency through Community Engagement: Training for Gugah Mandiri Cooperative in Jeneponto, South Sulawesi - Asri, Marselinus; Tandiayu, Bartholomeus (PT. Amirul Bangun Bangsa, 2024)
This article details a community service program aimed at improving the accounting skills of managers, administrative staff, and supervisors at the Gugah Mandiri cooperative in Jeneponto, South Sulawesi. The three-day training course covers essential accounting standards, how to use Accounting Software accurately, and relevant tax regulations. This initiative is designed to improve the financial management of cooperatives, thereby contributing to the overall efficiency and sustainability of cooperatives. Through a combination of lectures, practical exercises, and discussions, participants gained valuable knowledge and skills that are important for effective cooperative management. The training results highlight the importance of targeted educational interventions to support local economic development.